1990
DOI: 10.1159/000216116
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Functions in Recombinant Hirudin-Anticoagulated Blood

Abstract: The influence of genetically engineered recombinant hirudin (r-hirudin) on platelet functions was studied. Depending on the concentration, r-hirudin inhibits the thrombin-induced aggregation and 14C-serotonin secretion to the same extent as native hirudin. Comparative studies in blood anticoagulated by r-hirudin, heparin or citrate show a significantly lower spontaneous platelet aggregation in r-hirudinized blood. The extent of the ADP-induced aggregation is nearly the same in r-hirudinized, heparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
1
22
1
2
Order By: Relevance
“…Previous studies have established direct thrombin inhibitors such as lepirudin as anticoagulants for platelet function studies because these inhibitors, in contrast to citrate, keep up physiological levels of calcium ions and have no direct effect on platelets [4,[6][7][8]. In both sample tubes of this comparative study, lepirudin was used -in a liquid form in one tube and in a spray dried form in the other.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established direct thrombin inhibitors such as lepirudin as anticoagulants for platelet function studies because these inhibitors, in contrast to citrate, keep up physiological levels of calcium ions and have no direct effect on platelets [4,[6][7][8]. In both sample tubes of this comparative study, lepirudin was used -in a liquid form in one tube and in a spray dried form in the other.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the anticoagulant effects of hirudins showed that they are thrombin-spe cific inhibitors, which form tight stoichiomet ric complexes with thrombin whereby the ac tive center of the enzyme is blocked [10]. Thus, hirudin prevents not only fibrinogen clotting but also other thrombin-catalyzed haemostatic reactions such as activation of both clotting factors and platelets [11], The thrombin-induced platelet aggregation and re lease reaction are prevented in hirudinized blood [12][13][14], However, no references have been found in the literature about the effects of hirudin on the fibrinolytic system.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent thrombotic occlusion in extracorporeal circulation, higher hirudin doses are required than are necessary for the inhibition of venous thrombosis, as has al ready been demonstrated in rat models of arteriovenous shunt thrombosis [7], In our opinion, this is due to the role platelets play in thrombus formation. Because of the high affinity of thrombin for platelet membrane receptors, the platelet reaction initiated by thrombin is inhibited at higher r-hirudin concentrations only [10]. The platelet reac tion caused by collagen, ADP and other sub stances is not influenced by r-hirudin [11], Hirudin as anticoagulant in hemodialysis compares well with heparin, which has pre dominantly been used for this purpose so far.…”
Section: Discussionmentioning
confidence: 99%